Теоретичні засади дослідження соціального підприємництва в контексті маркетингу 3.0 - Seleznоva, Olha; Boiko, Olena; Bondar, Victoria (Dr. Viktor Koval, 2020)
Introduction. Modern development of socio-economic sector makes adjustments to market environment. Enterprises require expansion of their activities and feel necessity to diversify risks. Satisfaction of consumer needs is accompanied by introduction of innovations in various areas. Focusing on marketing 3.0, when market activity should not only ensure enterprise’s profitability, but also care about consumer and environment, is embracing more and more enterprises and becoming modern business responsibility. Therefore, the problem of social entrepreneurship research in context of sustainable development is becoming relevant and important. Aim and tasks. The main aim of this work is to formulate theoretical means for social entrepreneurship research, which should reveal peculiarities of tools to achieve global goals of sustainable development. To achieve this goal, the following tasks have been solved in this study: analysis of definitions and study the essence of “social entrepreneurship” concept; interconnection of social entrepreneurship goals with global goals of sustainable development and compliance with modern concept of marketing 3.0. Results. Research of “social enterprise” definition allows to define it as stable business structure, tended to self-development, which forms mechanism of social support and infrastructure development through close integration into social system. Social entrepreneurship is aimed at solving social problems and other goals of marketing 3.0. Social enterprise is considered in context of sustainable development, which is a concept that requires balance between satisfying current needs of people and protecting interests of future generations, ensuring their necessity for safe and healthy environment, and it must be able to contribute to global goals of sustainable development at local level. Conclusions. Social enterprises have become an acceptable mechanism for solving socio-economic problems, as they are developing and expanding new tools to achieve global goals of sustainable development at local level. Social  entrepreneurship has opportunity to involve socially vulnerable groups in public life and expand citizens’ activity. Social entrepreneurship today is aimed at positive social changes and providing basic human needs in an optimal way.